Official report of a goodwill and fact-finding mission to Guyana, September 30- October 5, 1990 (Caribbean Conference of Churches BridgetownBB, 1991)
Identyifies the psychological mood of the populace as that of hopelessness and sadness and attributes it to the three main factors - political i.e. the electoral processl the abuse of human and civil rights and the politicisation of every important aspect of public life - racial cleavages - and finally the economic collapse.
DC